Smart cane for the visually impaired and for people with low vision - Oni, Atib Mohammad; Debnath, Aditta; Fyaaz, Ahmad Ibrahim; Tiasha, Ifrit (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.